Severe aplastic anemia following liver transplantation in a patient with non-A-E fulminant hepatitis - Sema Aydoğdu; Gökhan TÜMGÖR; Deniz Yılmaz KARAPINAR; Bülent KARAPINAR; Çiğdem ARIKAN; Murat KILIÇ; Yeşim AYDINOK (Turkish Journal of Gastroenterology, 2019)
-